Occurrence and Diversity of CRISPR Loci in Lactobacillus casei Group - Yang, Lan; Li, Weixun; Ujiroghene, Obaroakpo Joy; Yang, Yang; Lu, Jing; Zhang, Shuwen; Pang, Xiaoyang; Lv, Jiaping (Frontiers in Microbiology, 2020)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) is an adaptive immune system that resists foreign genes through nuclease targeting in bacteria and archaea. In this study, we analyzed 68 strains of Lactobacillus casei group from the NCBI GenBank database, and bioinformatic tools were used to investigate the occurrence and diversity of CRISPR system. The results showed that a total of 30 CRISPR loci were identified from 27 strains. Apart from three strains which contained double loci with distinguishable distributed sites, most strains contained only one CRISPR locus. The analysis of direct repeat (DR) sequences showed that all DR could form stable RNA secondary structures. The CRISPR spacers showed diversity, and their origin and evolution were revealed through the investigation of their spacer sequences. In addition, a large number of CRISPR spacers showed perfect homologies to phage and plasmid sequences. Collectively, our results would contribute to researches of resistance in L. casei group, and also provide a new vision on the diversity and evolution of CRISPR/Cas system.